Secchi Depth with black and white difference combination at Ciwaka Reservoir - Forcep Indaryanto Rio Indaryanto (JURNAL PERIKANAN DAN KELAUTAN, 2015)
Secchi disk has long been used as a measure of water transparency because of its simplicity. Brightness is a portion of the light transmitted into the water. This study examines the differences in the brightness of the water with a combination of black and white case study in the Ciwaka reservoir, Walantaka, Serang – Banten Province. The study was conducted in May 2015. The observation point are in the inlet, middle and outlet area. Observations secchi brightness using four different colors: black (Hi), white (Pu), 2 black-and-white shaded (A2) and 4 shaded black-and-white (A4). The experimental design used was completely randomized factorial design with color factor secchi and observation points. Secchi disk affect the value of color brightness or Secchi depth, a good color to use for the waters of the reservoir is a combination of black and white either 2 or 4 shaded. The central region and the outlet has a low brightness value, this is due to the accumulation of organic and inorganic materials in the region.